2015
DOI: 10.1080/20445911.2015.1118107
|View full text |Cite
|
Sign up to set email alerts
|

Is more choice always worse? Age differences in the overchoice effect

Abstract: Current research on the overchoice effect has been conducted from an adult point of view and with adult subjects. This study investigates whether children, adolescents and seniors suffer the same negative consequences as adults when facing an over-abundance of choice. Findings show that the overchoice effect does not extend to all age groups. While adolescents appear to be affected by the phenomenon in a very similar way as adults, children and seniors seem to be immune to it. Theoretical and practical implica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 60 publications
1
17
0
Order By: Relevance
“…Some of these authors found no significant correlation (Parker et al, 2007), while others found lower maximizing tendencies in older adults compared to younger adults (Tanius et al, 2009; Bruine de Bruin et al 2016). These latter results align well with studies showing a higher satisfaction of seniors compared to younger adults after choosing from an overabundance of options (see Misuraca, Teuscher, & Faraci, 2016).…”
Section: Tell Me Which Scale You Use and I Tell You Who's Happier Andsupporting
confidence: 90%
“…Some of these authors found no significant correlation (Parker et al, 2007), while others found lower maximizing tendencies in older adults compared to younger adults (Tanius et al, 2009; Bruine de Bruin et al 2016). These latter results align well with studies showing a higher satisfaction of seniors compared to younger adults after choosing from an overabundance of options (see Misuraca, Teuscher, & Faraci, 2016).…”
Section: Tell Me Which Scale You Use and I Tell You Who's Happier Andsupporting
confidence: 90%
“…Promoting adjustment to college is a key factor strictly related to academic performance, achievement, and success, reducing withdrawal, and behavioral and/or mental disengagement. Future research may reproduce a similar study in public universities and evaluate the role of further variables (e.g., choice overload when choosing university classes [ 47 ], self-actualization [ 48 ], and boredom [ 49 ]). In addition, it may be useful to utilize a prospective design in which self-ratings would be collected before students start studying at college, to allow inferences about causation: sure enough, results from concurrent designs could be ambiguous in that assessments of personality might be reactions to adjustment status rather than predictors of it [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies 1 and 2 aim to test whether the presence of a brand name mitigates the adverse consequences of choice overload in adolescents. In line with prior research on choice overload (Iyengar and Lepper, 2000;Misuraca et al, 2016a;Misuraca and Teuscher, 2013), in both studies, we compared betweensubjects differences in the levels of reported dissatisfaction, difficulty and regret in a choice condition where adolescents chose among either 6 or 24 options associated with brand names and in another choice condition where adolescents chose among the same 6 or 24 options but not associated with brand names. In the first study, participants chose energy bars.…”
Section: Overview Of Studiesmentioning
confidence: 98%
“…Given the profound impact of teen spending on the consumer economy, investigating the purchase behavior of adolescents when facing an overabundance of choice represents an important topic that can provide helpful insight for marketers, at both the theoretical and managerial levels. Moreover, prior research has shown that age is an important moderator variable of choice overload (Misuraca et al, 2016a). In particular, Misuraca et al (2016a) investigated the reactions of children, adolescents, adults and seniors when facing a large (versus a small) choice set and found that adults and adolescents suffer the same negative consequences of an overabundance of choice (i.e.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation